Exploring the Long-Term Evolution of Trade Survival - Wolfgang Hess; Maria Persson (Research Institute of Industrial Economics (IFN), 2011)
Aiming to explore how the survival of trade flows has evolved over time, we analyze a rich data set of detailed imports to individual EU15 countries from 140 non-EU exporters, covering the period 1962-2006. We find that short duration is a persistent characteristic of trade throughout the extended time period that we study: in general only 40 percent of trade flows survive the first year of service, and this share has not changed much since the 1960s. However, this observed constancy is the result of two underlying trends that work in opposite directions. On the one hand, positive trends in several of the observed explanatory variables - which in turn influence the hazard of trade flows dying in a negative direction - imply that the hazard tends to decrease over calendar time. On the other hand, there is also a positive trend in the hazard due to calendar year-specific unobserved factors. Holding all observed determinants constant, the probability of a trade flow dying in its first year increases from 34% at the beginning of the period to 90% at the end.
Keywords: C41; F10; F14; 330; Duration of Trade; Survival; Entry and Exit; European Union; Discrete-Time Hazard Models; Internationale Wirtschaftsbeziehungen; Import; Statistische Bestandsanalyse; EU-Staaten